Determinants influencing patients’ perceptions of radiology examination result waiting time: A cross-sectional study - Zulkarnain, Dedy; Satar, Yuli Prapanca; Wulandari, Sonya Dewi (School of Health Sciences Al-Ma'arif, 2026)
Background: Radiology examination result waiting time represents an important indicator of healthcare service efficiency and patient-centered quality. Prolonged waiting time may influence patient satisfaction, trust in healthcare services, and clinical decision-making processes. Organizational factors such as human resources, infrastructure, and equipment readiness are considered critical determinants affecting patients’ perceptions of radiology service timeliness. Objective: This study aimed to investigate factors associated with patients’ perceptions of radiology waiting times. Methods: This analytic observational study employed a cross-sectional design conducted in August 2025 at the Radiology Installation of RSUD Siti Fatimah, South Sumatra Province. A total of 160 patients who had undergone radiological examinations were recruited using accidental sampling. Data were collected through a validated and reliable structured questionnaire assessing human resources, building and infrastructure, radiology equipment, and patients’ perceptions of waiting time. Data analysis included descriptive statistics, Chi-square tests for bivariate associations, and multiple logistic regression using the backward likelihood ratio method to identify dominant predictors. Results: Human resources showed the strongest association with patients’ perceptions of radiology examination result waiting time (OR = 27.607; p < 0.001), followed by building and infrastructure factors (OR = 5.432; p = 0.048). Radiology equipment demonstrated a significant association in bivariate analysis but was not retained as a dominant predictor in the final multivariate model. These findings indicate that staff professionalism, responsiveness, communication quality, and service environment play substantial roles in shaping patient perceptions of radiology service efficiency. Conclusion: Critical role of human resources and physical facilities in improving the quality of radiology services. Strategic initiatives should focus on strengthening both the quality and quantity of human resources, along with maintaining adequate supporting facilities, to ensure timely and optimal radiology service delivery.